Impact of Frailty on Outcomes Following Spine Surgery: A Prospective Cohort Analysis of 668 Patients. Issue 3 (28th December 2020) - Agarwal, Nitin; Goldschmidt, Ezequiel; Taylor, Tavis; Roy, Souvik; Dunn, Stefanie C Altieri; Bilderback, Andrew; Friedlander, Robert M; Kanter, Adam S; Okonkwo, David O; Gerszten, Peter C; Hamilton, D Kojo; Hall, Daniel E
Abstract: BACKGROUND: With an aging population, elderly patients with multiple comorbidities are more frequently undergoing spine surgery and may be at increased risk for complications. Objective measurement of frailty may predict the incidence of postoperative adverse events. OBJECTIVE: To investigate the associations between preoperative frailty and postoperative spine surgery outcomes including mortality, length of stay, readmission, surgical site infection, and venous thromboembolic disease. METHODS: As part of a system-wide quality improvement initiative, frailty assessment was added to the routine assessment of patients considering spine surgery beginning in July 2016. Frailty was assessed with the Risk Analysis Index (RAI), and patients were categorized as nonfrail (RAI 0-29) or prefrail/frail (RAI ≥ 30). Comparisons between nonfrail and prefrail/frail patients were analyzed using Fisher's exact test for categorical data or by Wilcoxon rank sum tests for continuous data. RESULTS: From August 2016 through September 2018, 668 patients (age of 59.5 ± 13.3 yr) had a preoperative RAI score recorded and underwent scheduled spine surgery. Prefrail and frail patients suffered comparatively higher rates of mortality at 90 d (1.9% vs 0.2%, P < .05) and 1 yr (5.1% vs 1.2%, P < .01) from the procedure date. They also had longer in-hospital length of stay (LOS) (3.9 d ± 3.6 vs 3.1 d ± 2.8, P < .001) and higher rates of 60 d (14.6% vs 8.2%, P < .05) and 90 d (15.8% vs 9.8%, P < .05) readmissions. CONCLUSION: Preoperative frailty, as measured by the RAI, was associated with an increased risk of readmission and 90-d and 1-yr mortality following spine surgery. The RAI can be used to stratify spine patients and inform preoperative surgical decision making. Graphical Abstract: